Pervasive horizontal transmission of Wolbachia in natural populations of closely related and widespread tropical skipper butterflies - Pedro Ribeiro; Anzhelika Butenko; Daniel Linke; Hamid Reza Ghanavi; Joana Isabel Meier; Niklas Wahlberg; Pável Matos-Maraví (BMC Microbiology)
Abstract Background The endosymbiotic relationship between Wolbachia bacteria and insects has been of interest for many years due to their diverse types of host reproductive phenotypic manipulation and potential role in the host’s evolutionary history and population dynamics. Even though infection rates are high in Lepidoptera and specifically in butterflies, and reproductive manipulation is present in these taxa, less attention has been given to understanding how Wolbachia is acquired and maintained in their natural populations, across and within species having continental geographical distributions. Results We used whole genome sequencing data to investigate the phylogenetics, demographic history, and infection rate dynamics of Wolbachia in four species of the Spicauda genus of skipper butterflies (Lepidoptera: Hesperiidae), a taxon that presents sympatric and often syntopic distribution, with drastic variability in species abundance in the Neotropical region. We show that infection is maintained by high turnover rates driven mainly by pervasive horizontal transmissions, while also presenting novel cases of double infection by distantly related supergroups of Wolbachia in S. simplicius. Conclusions Our results suggest that Wolbachia population dynamics is host species-specific, with genetic cohesiveness across wide geographical distributions. We demonstrate that low coverage whole genome sequencing data can be used for an exhaustive assessment of Wolbachia infection in natural populations of butterflies, as well as its dynamics in closely related host species. This ultimately leads to a better understanding of the endosymbiotic population dynamics of Wolbachia and its effects on the host’s biology and evolution.